24M Progress Report. Period concerning this report: 01.01.2019-31.12.2019. - Glaskova-Kuzmina, Tatjana (Zenodo, 2019)
During the second year of the project the main purpose was to design and develop smart fibre-reinforced plastic (FRP) plate by using the most environmentally stable nanocomposite (NC) configuration. As a result, within the support of collaboration partner Institute for Polymers, Composites and Biomaterials (IPCB, Portici, Italy) during Mobility#4 four basalt FRP plates were produced: two [0]8 plates impregnated with the epoxy or the NC, and two [0/45/90/-45]2 also impregnated with the epoxy or the NC, and two [0/45/90/-45]2. Additionally, a set of the specimens for the epoxy and epoxy filled with 0.1 wt.% of hybrid nanofiller (carbon nanotubes and nanofibers in the ratio 1:1) was developed for full year environmental ageing. The characterization of flexural, thermophysical and electrical properties was performed for all materials in uncondensed state (before the environmental ageing). After that the first season of environmental ageing (summer, water absorption at room temperature) has been started for all materials. Moreover, water absorption at 20 and 50 ºC until equilibrium has been performed for all materials.
2. gada progresa atskaite
Keywords: 24M progress report; POSTDOC Latvia